Antimicrobial Properties of Glass Surface Functionalized with Silver-doped Terminal-alkynyl Monolayers - Tahir, Muhammad Nazir; Jeong, Daham; Kim, Hwanhee; Yu, Jae-Hyuk; Cho, Eunae; Jung, Seunho (Bulletin of the Korean Chemical Society, 2014)
Glass discs functionalized with alkynyl (GDA) terminated monolayers were prepared and incubated in AgNO 3 solution (GDA-Ag). The modified functional glass surfaces were characterized by X-ray photoelectron microscopy (XPS). The potential of GDA and GDA-Ag as antimicrobial surfaces was investigated. Anti- microbial efficacies of GDA against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Bacillus cereus, and Candida albicans was relatively low ranging from 4.67 to 17.00%. However, the GDA- Ag was very effective and its antimicrobial efficacy ranged from 99.90 to 99.99% against the same set of microbial strains except for C. albicans where it was 95.50%. The durability of the Ag bonded to the terminal alkynyl groups was studied by placing the GDA-Ag in PBS buffer solution (pH 7.4) for two weeks. Initially, the silver release was relatively fast, with 40.05 ppb of silver released in first 24 h followed by a very slow and constant release. To study the potential of GDA-Ag for medical applications, in vitro cytotoxicity of GDA-Ag against Human Embryonic Kidney 293 (HEK293) cell lines was studied using WST-assay. The cytotoxicity of the GDA-Ag was very low (5%) and was almost comparable to the control (blank glass disc) indicating that GDA-Ag has a promising potential for medical applications. KCI Citation Count: 2